PELAYANAN BUNDA TERESA KEPADA KAUM LEMAH SEBAGAI INSPIRASI BAGI PELAYANAN KATEKIS DEWASA INI - Meliana Hoar Bria; Agustinus Supriyadi (Bahasa Indonesia, 2019)
In common life, man is guided and directed to love, attention and noble servexes. it is because to serve the others is a very noble and beautiful task in the eyes of God Mother Teresa is a holy and player person who is willing to dedicate her self totally to the poor and to God. Due to so much of her love to the the vurnerable. Mother Teresa chose to leave her family and forget about personal wealth for her total love, attention and services to the poor who need these services very much. Mother Teresa spirit of service is the foundation of her strength and inspiration. which should be imitated by today's catechists. Her core spirituality is happy, joy, love, sacrifice and smiling. The sixth point of her spirituality is a source of inspiration and encouragement for her to serve the poor. A catechist has a heavy responsibility to the people, especally to the poor. For this, a cathecist must have a sense and a willingness to learn continuously as to accept such advice of.friends with an openly arm. In addition, a catechist should be able to establish a nice relationships with people who work in the filed of services. Just as Mother Teresa, it is impossible fa a catechist to work alone. Therefore, a catechists need to cooperate with others in order to improve his or her services to the others, especially to the poor.